Correlation between maternal thyroid stimulating hormone and birth weight of neonate - Shettian, Nishita; Pavuluri, Hema Venkata Naga Sai Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of this study is to determine the pregnancy outcomes in women with thyroid disorders. Methods: This is a retrospective observational study conducted in the department of obstetrics and gynaecology of AJ institute of medical sciences and research centre from the month of March to September 2021. The first trimester thyroid stimulating hormone (TSH) level and birth weight of new born is collected from hospital records, study participants included all the pregnant mothers who were admitted and delivered in the labour ward of AJ institute of medical sciences Results: According to our study low birth weight in neonates in euthyroid, hypothyroid, hyperthyroid participants were 21.4%, 61.5%, and 100% respectively. Conclusions: This study indicates that there is an association between maternal thyroid levels and neonatal birth weight. A higher TSH concentration during first trimester of pregnancy is associated with low birth weight. Based on these findings, it is recommended that maternal thyroid levels be monitored closely in the first trimester and initiate timely treatment in case of altered thyroid levels during pregnancy in order to have a healthy pregnancy and healthy baby with no compromise in the fetal weight.